The management conception in the School Formation of Managers of Basic Education of the MEC: an analysis of the program - Fernandes, Tania da Costa; França, Juliana Utrera (Faculdade de Filosofia e Ciências, 2019)
Resulting from a bibliographical and documentary research and based on a critical materialist approach, this article aims to present general aspects that characterize the specialization course in school management, offered by the Ministry of Education, in the School Program of Managers of Basic Education, problematizing its conception management. Because of the analysis, the guidelines of the course are based, above all, on a neoliberal political-economic and educational conception, with emphasis on managerialist management, which is justified to meet the new demands for education. However, considering that this managerialist conception is opposed to the principles of democratic management – guaranteed in the Federal Constitution (1988) and the Law on Guidelines and Bases of National Education (LDBEN, 1996) – and therefore reduces the continuing training of managers to the dictates of competitiveness, productivity and meritocracy, the article seeks to collaborate for the reflection of educators and managers as to the potentialities and weaknesses of a formation according to the profile defined in the Program of managers of basic education. Recebido em: 16/02/2018.Aprovado em: 13/06/2019.